Novel Functional Renal PET Imaging With 18F-FDS in Human Subjects - Werner, Rudolf A; Ordonez, Alvaro A; Sanchez-Bautista, Julian; Marcus, Charles; Lapa, Constantin; Rowe, Steven P; Pomper, Martin G; Leal, Jeffrey P; Lodge, Martin A; Javadi, Mehrbod S; Jain, Sanjay K; Higuchi, Takahiro (Clinical nuclear medicine, 2019)
The novel PET probe 2-deoxy-2-F-fluoro-D-sorbitol (F-FDS) has demonstrated favorable renal kinetics in animals. We aimed to elucidate its imaging properties in 2 human volunteers. F-FDS was produced by a simple 1-step reduction from F-FDG. On dynamic renal PET, the cortex was delineated and activity gradually transited in the parenchyma, followed by radiotracer excretion. No adverse effects were reported. Given the higher spatiotemporal resolution of PET relative to conventional scintigraphy, F-FDS PET offers a more thorough evaluation of human renal kinetics. Due to its simple production from F-FDG, F-FDS is virtually available at any PET facility with radiochemistry infrastructure.